1991
DOI: 10.1099/00221287-137-5-1067
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of the Pasteurella multocida toxin in a toxin-producing strain

Abstract: Toxigenic strains of Pasteurella multocida produce the 147 kDa protein Pasteurella multocida toxin (PMT) which is responsible for the osteoclastic bone resorption in progressive atrophic rhinitis in pigs and induces such resorption in all experimental animals tested so far. In the present study we have carried out immunocytochemistry on formaldehyde-and glutaraldehyde-fixed ultracryocut P. multocida using a pool of monoclonal antibodies against different epitopes on PMT as the first layer and affinity purified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that PMT is not secreted from in vitro grown cells (Nakai et al ., 1985; iDali et al ., 1991). Thus, electron microscopy demonstrated that the toxin was cytoplasmic in P. multocida , and that no toxin could be detected on intact undamaged P. multocida (iDali et al ., 1991). Furthermore, the toxin has no apparent signal sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that PMT is not secreted from in vitro grown cells (Nakai et al ., 1985; iDali et al ., 1991). Thus, electron microscopy demonstrated that the toxin was cytoplasmic in P. multocida , and that no toxin could be detected on intact undamaged P. multocida (iDali et al ., 1991). Furthermore, the toxin has no apparent signal sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin is a modular protein, with domains for cell‐binding/internalization at the N‐terminus and for enzymatic activity at the C‐terminus (Busch et al ., 2001; Pullinger et al ., 2001), and therefore has the characteristics of a secreted exotoxin. However, it is not secreted from the bacteria during in vitro culture, and ultrastructural studies of toxigenic P. multocida demonstrated that PMT was localized in the bacterial cytoplasm (Nakai et al ., 1985; iDali et al ., 1991).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, secretion of some exotoxins is dependent on the phase of growth of the bacterium and its cultural conditions (Wretling & Heden 1933, O'Reilly & Day 1983, Idali et al 1991) while other toxins remain in the cytoplasm and are released only after cell lysis. In fact, when the ECP of Corynebacterium aquaticum from striped bass were collected at 24 h (instead of at 48 h), the protein content and proteolytic activity of the ECP were very low (0.2 mg ml-' and 1.2 units ml-' respectively), no cytotoxins were detected, and the ECP lacked toxicity for fish.…”
Section: Pathogenicity Of Corynebacterium Aquaticum For Fish and Micementioning
confidence: 99%
“…Ultrastructural studies of toxigenic P. multocida showed that PMT was localized in the cytoplasm of the bacteria [217,218]. Although it is known that PMT is expressed under noninducing conditions, it is possible that phage induction results in PMT release from cells during infection.…”
Section: Pmt Production and Releasementioning
confidence: 99%